Konsep ZIKR, PIKR & MIKR: Pendekatan Profesional Bank Muamalat Indonesia (BMI) - Mohamad Sabri Haron, (Universiti Kebangsaan Malaysia, 2009)
Despite the crisis and economic turmoil that hits many Asian countries in1999, Bank Muamalat Indonesia (BMI) remains stable as compared to other banks. More than that BMI emerges as an established syariah bank in Indonesia. The mechanism behind this is related to the practice of the concepts of ZIKR, PIKR and MIKR. This paper discusses the concept of ZIKR, PIKR and MIKR practiced by BMI. The concept which is known as The Celestial Management is proven to be effective in short period of time since its implementation